Revision of the Nearctic species of Gimnomera Rondani (Diptera: Scathophagidae), with morphological phylogeny and DNA barcodes - Chagnon, Marie-Eve; Sinclair, Bradley J. (Zootaxa, 2020)
The Nearctic species of Gimnomera Rondani are revised and includes eight species, of which three are new to science (G. aquilonia sp. nov., G. cerea (Coquillett), G. cuneiventris (Zetterstedt), G. incisurata Malloch, G. subvittata (Malloch), G. terrywheeleri sp. nov., G. tibialis (Malloch), G. vockerothi sp. nov.). Gimnomera cuneiventris is newly recognized as Holarctic in distribution. Gimnomera fasciventris Malloch is removed and transferred to the genus Acerocnema, comb. nov. An additional Nearctic species is recognized but not described due to lack of male specimens. Species descriptions, diagnoses and distribution maps are presented, including images of the male terminalia as well as additional diagnostic characters. A key to the Nearctic species is also provided. A morphological cladistic analysis of 12 species reveals that the Nearctic and Palearctic species do not form separate monophyletic groups. COI mitochondrial DNA barcode sequences were obtained for eight Nearctic species of Gimnomera.